Determination of Bancassurance Ujrah at PT Bank Syariah Indonesia KCP Purwokerto Sudirman - Muhammad, Fikra Adib; Maulana, Ade; Fahmi, Fikri Afthon (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2025)
Bancassurance is a form of cooperation between banks and insurance companies in marketing insurance products through banking networks. From a sharia economic law perspective, bancassurance practices must be based on the principles of clarity of contract and transparency of information as stipulated in the Indonesian Ulema Council's National Sharia Board Fatwa Number 139/DSN-MUI/VIII/2021 concerning the Marketing of Insurance Products Based on Sharia Principles, which allows the use of ijārah contracts, wakālah bi al-ujrah, and ju‘ālah contracts according to the context of the cooperation. However, in practice at PT Bank Syariah Indonesia KCP Purwokerto Sudirman, there were issues related to the determination of ujrah sourced from the customer's initial contribution, which was not clearly stated in the insurance cover note. This condition raises questions about customer rights and the validity of the contract from a sharia perspective, particularly regarding the potential element of gharar. This research is field research with a normative juridical approach and descriptive-analytical methods. Data collection was carried out through observation, interviews, and documentation. The results showed that bancassurance practices were carried out through cooperation with PT Asuransi Jiwa Syariah Al Amin using a reference business model. This legal relationship places the bank as the party that receives ujrah based on a ju'ālah contract for the successful achievement of financing targets accompanied by insurance. Because ujrah is an agreement between the bank and the insurance company, customers have no legal standing in the contract. Therefore, the ambiguity of ujrah in the cover note cannot be categorized as gharar that invalidates the contract as long as the rights and obligations of customers are explained transparently in accordance with sharia principles